PENERAPAN MODEL PEMBELAJARAN MATEMATIKA TERHADAP HIGHER ORDER THINKING SKILLS (HOTS) SISWA KELAS IV MI NEGERI PUNGGELAN BANJARNEGARA TAHUN PELAJARAN 2017/2018 - HARYANTO, ANDRI; MULYANI, PAMUNGKAS STIYA (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2019)
This study aims to determine the learning process with a realistic mathematical learning model that is applied to improve students 'HOTS and to determine the effect of a realistic mathematics learning model on students' HOTS. This study uses a quantitative approach with a quasi-one group experiment, with a sample of 30 students, this sample was taken from the population of all MI Negeri Punggelan Banjarnegara students in the academic year 2017/2018. Research data in the form of high-level students' ability to think from the results of multiple choice questions. The analysis technique used is quantitative analysis with the